A COMPARATIVE STUDY OF SAFETY AND EFFICACY OF 30% FORMIC ACID WITH 85% FORMIC ACID IN THE TREATMENT OF PALMOPLANTAR WARTS. - Dsouza, Deepti C; M Ali, Neema (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Warts are a common skin disease seen by dermatologists. It is an infection caused by different strains of human papilloma virus. The presence of various topical and systemic treatments for warts is a testament to the lack of a rapid, simple, uniformly effective, inexpensive, nonscarring, and painless treatment. The purpose of this study was to compare the safety and efficacy of 85% formic acid with 30% formic acid on palmoplantar warts. Methods: A non-randomized, open trial was performed in 30 patients with common warts attending Father Muller's Medical College Hospital, Mangalore. 15 patients received 85% formic acid application, and 15 patients received 30% formic acid using a to puncture technique every day. Results: About 73.3% in Group I and 73.3% in Group II showed disappearance of warts at the end of 3 months. No major side-effects were seen at the end of therapy in either group. Conclusions: The results show that both 30% and 85% formic acid application are a safe, economical, and effective alternative in the treatment of common warts with few side-effects and 30% formic acid may be an effective replacement of 85% formic acid. A study with more number of patients is needed to see the efficacy of this treatment. Keywords: Warts, Formic acid, Palmoplantar warts.